Enterococcal endocarditis in the beginning of the 21st century: analysis from the International Collaboration on Endocarditis‐Prospective Cohort Study. (20th March 2013) - Chirouze, C.; Athan, E.; Alla, F.; Chu, V. H.; Ralph Corey, G.; Selton‐Suty, C.; Erpelding, M.‐L.; Miro, J. M.; Olaison, L.; Hoen, B.; ,; Paul, M.
Abstract Enterococci are reportedly the third most common group of endocarditis‐causing pathogens but data on enterococcal infective endocarditis (IE) are limited. The aim of this study was to analyse the characteristics and prognostic factors of enterococcal IE within the International Collaboration on Endocarditis. In this multicentre, prospective observational cohort study of 4974 adults with definite IE recorded from June 2000 to September 2006, 500 patients had enterococcal IE. Their characteristics were described and compared with those of oral and group D streptococcal IE. Prognostic factors for enterococcal IE were analysed using multivariable Cox regression models. The patients' mean age was 65 years and 361/500 were male. Twenty‐three per cent (117/500) of cases were healthcare related. Enterococcal IE were more frequent than oral and group D streptococcal IE in North America. The 1‐year mortality rate was 28.9% (144/500). E. faecalis accounted for 90% (453/500) of enterococcal IE. Resistance to vancomycin was observed in 12 strains, eight of which were observed in North America, where they accounted for 10% (8/79) of enterococcal strains, and was more frequent in E. faecium than in E. faecalis (3/16 vs. 7/364, p 0.01). Variables significantly associated with 1‐year mortality were heart failure (HR 2.4, 95% CI 1.7—3.5, p <0.0001), stroke (HR 1.9, 95% CI 1.3—2.8, p 0.001) and age (HR 1.02 per 1‐year increment, 95% CI 1.01—1.04, p 0.002). Surgery was not associated with better outcome. Enterococci are an important cause of IE, with a high mortality rate. Healthcare association and vancomycin resistance are common in particular in North America.